THE EFFECT OF CARBOXYMETHYL CHITOSAN/AMORPHOUS CALCIUM PHOSPHATE TO GUIDE TISSUE REMINERALIZATION OF DENTIN COLLAGEN - ANNISA, ROSDIANA NURUL; DJAUHARIE, NILAKESUMA; SUPRASTIWI, ENDANG; AVANTI, NORMA (International Journal of Applied Pharmaceutics, 2019)
Objective: Carboxymethyl chitosan/amorphous calcium phosphate (CMC/ACP) can replace the role of dentine matrix protein 1. Guided tissue remineralization (GTR) is a method of extrafibrillar and intrafibrillar collagen remineralization. This study analyzed the ability of CMC/ACP to achieve intrafibrillar and extrafibrillar remineralization on demineralized dentin. Methods: We divided 12 demineralized occlusal cavities into four groups: 7 days control group, 14 days control group, 7 days CMC/ACP group, and 14 days CMC/ACP group. In the control group, the cavities were directly filled with temporary restoration material, while the cavities of the CMC/ACP groups first underwent application of CMC/ACP and were then filled with temporary restoration material. All samples were stored in a 37°C shaking incubator. 12 samples were analyzed by energy-dispersive X-ray (EDX) spectroscopy and four were analyzed by transmission electron microscope (TEM). Results: From day 7 to day 14, there was a significant increase in calcium and phosphate levels within the CMC/APC groups. The phosphate levels were much lower than the calcium or minerals formed on the 7th day, in the form of hydroxyapatite. TEM analysis shows that the CMC/ACP group exhibited more intrafibrillar and extrafibrillar remineralization. Conclusion: CMC/ACP can improve the GTR process.